Biofuel production in South Africa. Issue 2 (March 2011) - Funke, T; Klein, P; Meyer, F
The production of biofuels in South Africa has been largely hampered by a government strategy that lacks the incentives required in order to initiate large-scale developments. The concern of the impact on food security and the risk to the consumer have been instrumental in shaping this strategy, but the question as to whether these have been based on emotion rather than fact remains. It is hypothesized that the strategy has been formulated owing to the distorted information that various individual role players have supplied and, as a result, its entire development process has been misaligned with the needs of the industry. This article aims to sketch and review the problems that are hampering the development of the sector. The article also reviews actual data from projects and comments on alternative policy options that are available to the government, should it choose to establish a sustainable and vibrant biofuels sector.